"Proceedings of the International Conference, 2004 on Business & Finance, Vol.I: Banking, Insurance and Financial Services" - Narender (Vunyale) Ed.; Amalraj (Hilda) Ed. ("52, Nagarjuna Hills,Hyderabad - 500 082", 2005)
Proceedings ; International Conference
50
Keywords: Proceedings ; International Conference